Issues In The Implementation Of Industrial Sertu In Malaysia - Mohd Mahyeddin Mohd Salleh; Mustafa 'Afifi Bin Ab. Halim; Sumaiyah Abd Aziz; Hasdhatul NorAliah Md Said (Usuli Faqih Research Centre PLT, 2024)
Indexed by MyCite